Le prix de l’ostracisme de Cuba de l’OEA en 1962: les dessous de la conférence de Punta del Este - Wien Weibert Arthus (Nuevo mundo - Mundos Nuevos, 2017)
On January 30, 1962, Cuba was expelled from the Organization of American States (OAS) on the basis that “the Castro regime was an ally of the Sino-Soviet bloc” in violation of the Inter-American Treaty of Reciprocal Assistance commonly known as the Rio Treaty. At a ministerial conference held in Punta del Este in 1962, two-thirds of the OAS members (that is to say fourteen countries) approved a resolution excluding Cuba from the Inter-American system. By this act, the United States won a battle that lasted two years and whose main objective was to ostracize Cuba from the hemispheric system to give a strong signal to Fidel Castro and the potential pro-communist revolutionary in the region. The underside of the Punta del Este Conference shows that the United States achieved a victory, “the kind that we cannot be proud of”, wrote a member of the U.S. delegation Samuel Belk to President John F. Kennedy. The archives confirm that the United States did not skimp to pressure some delegations and to monetize certain countries in order to bring them to vote in favor his position against Cuba.